Distribution of coconut Lacewing Bug Stephanitis Typicus Distant and its natural enemy complex and assessment of biocontrol potential of the major natural enemies - Unnimon N K (Department of Agricultural Entomology, College of Horticulture, 1994)
A study on the distribution of the coconut lacewing bug Stephanitis typicus and its natural enemy complex was carried out during the period 1991-92 at four selected root (wilt) prone districts of kerala . The bio-control potential of the major identified natural enemies were also carried out during the same period . The results revealed that population of S.typicus showed a fluctuation throughout the year . The population was higher in the field during the dry seasons and it was at lower levels in rainy periods. The numbers of the pests increased from January onwards and recorded its maximum in March-April. The population started decreasing from May onwards and recorded the lowest level in June-July . From August the number of pest again started increasing and reached the second maximum in September - October. The level of population recorded was lowest in November- December. Congregation of S. typicus was observed in higher numbers on the inner whorls of coconut crown. Compared to leaves of inner whorls, the number of pest were fewer in middle and outer whorls. Natural enemy population was observed to remain stagnant throughout the year. Only a slight fluctuation was recorded in population of natural enemies , in accordance with the increased level of pest population . Generally a low level of natural enemy population was observed in the field throughout the study period . Rearing of S. typicus in glasshouse condition on different host plants like coconut , turmeric and arrowroot showed the preference by the pest to the coconut plants. Compared to other host plants the multiplication and survival of the pest was more on coconut plants.